A rare case of osteomyelitis and tenosynovitis in secondary syphilis. (2020) - Nelson, Taylor B.; Roland, William
Abstract: We describe a case of secondary syphilis presenting with osteomyelitis and tenosynovitis of the thumb. With appropriate therapy, the patient's symptoms resolved and seroreversion occurred. MRI showed improvement with treatment. This case highlights the importance of early diagnosis and appropriate therapy in this unusual presentation of syphilis.